Modeling of magnetic sensitivity of the metal-oxide-semiconductor field-effect transistor with double gates - Ghanim Thiab Hasan; Ali Hlal Mutlaq; Kamil Jadu Ali; Mohammed Ayad Saad (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In this paper, we investigated the effect of magnetic field on the carrier transport phenomenon in metal-oxide-semiconductor field-effect transistor (MOSFET) with double gates by examining the behavior of the semiconductor under the Lorentz force and a constant magnetic field. Various behaviors within the channel have been simulated including the potential distribution, conduction and valence bands, total current density, total charge density and the magnetic field. The results obtained indicate that this modulation affects the electrical characteristics of the device such as on-state current (ION), subthreshold leakage current (IOF), threshold voltage (VTh), and the Hall voltage (VH) is induced by the magnetic field. The change in threshold voltage caused by the magnetic field has been observed to affect the switching characteristics of the device, such as speed and power loss, as well as the threshold voltage VTh and (ION/IOF) ratio. Note that it is reduced by 10-3 V. 102 for magnetic fields of ±6 and ±5.5 tesla respectively.